Usborne illustrated Hans Christian Andersen's fairy tales - Milbourne, Anna; Parreño, Fran Doherty, Gillian Brocklehurst, Ruth Andersen, H. C. (Usborne London, 2011)
This illustrated book contains a collection of fairy tales by Hans Christian Andersen retold for younger readers